Nanovesicles released by OKT3 hybridoma express fully active antibodies. (1st January 2021) - Logozzi, Mariantonia; Di Raimo, Rossella; Properzi, Francesca; Barca, Stefano; Angelini, Daniela F.; Mizzoni, Davide; Falchi, Mario; Battistini, Luca; Fais, Stefano
Abstract: Recent findings have shown that nanovesicles preparations from either primary immune cells culture supernatants or plasma contain immunoglobulins, suggesting that a natural way of antibody production may be through exosome release. To verify this hypothesis, we used the OKT3 hybridoma clone, which produces a murine IgG2a monoclonal antibody used to reduce rejection in patients undergoing organ transplantation. We showed exosome-associated immunoglobulins in hybridoma supernatants, by Western blot, nanoscale flow cytometry and immunocapture-based ELISA. The OKT3-exo was also being able to trigger cytokines production in both CD4 and CD8 T cells. These results show that nanovesicles contain immunoglobulin and could be used for immunotherapy. These data could lead to a new approach to improve the effectiveness of therapeutic antibodies by exploiting their natural property to be expressed on nanovesicle membrane, that probably render them more stable and as a consequence more capable to interact with their specific ligand in the best way.